1997
DOI: 10.1074/jbc.272.12.7968
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Regulatory Aspects of the Human Intestinal Mucin Gene (MUC2) Locus

Abstract: The human MUC2 gene maps to chromosome 11p15, where three additional mucin genes have been located, and encodes the most abundant gastrointestinal mucin normally expressed in the intestinal goblet cell lineage. However, in pathological conditions, including colorectal cancer, MUC2 can be abnormally expressed. Therefore, it is of considerable interest to understand the regulation of the MUC2 gene and how the mechanism is altered in colon cancer. Toward this goal, we have isolated a group of overlapping clones (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…Individual colonies were isolated, expanded and further characterized. Induction of cells with TPA and forskolin was for 8 h as previously described (Velcich and Augenlicht, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Individual colonies were isolated, expanded and further characterized. Induction of cells with TPA and forskolin was for 8 h as previously described (Velcich and Augenlicht, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we investigated whether expression of DCC was mechanistically linked to the elaboration of the goblet cell phenotype. We have previously shown that HT29 cells can be induced to express a high level of MUC2 mRNA and protein, which represents the major form of colonic mucin, in response to forskolin and TPA (Velcich and Augenlicht, 1993). Thus, we determined whether the DCC + clones expressed MUC2 mRNA constitutively, or whether DCC could potentiate the responses to treatment with forskolin and TPA.…”
Section: Expression and Goblet Cell DI Erentiationmentioning
confidence: 98%
See 3 more Smart Citations